2015
DOI: 10.1016/j.ajog.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and metaanalysis of genetic association studies of urinary symptoms and prolapse in women

Abstract: ObjectiveFamily studies and twin studies demonstrate that lower urinary tract symptoms and pelvic organ prolapse are heritable. This review aimed to identify genetic polymorphisms tested for an association with lower urinary tract symptoms or prolapse, and to assess the strength, consistency, and risk of bias among reported associations.Study DesignPubMed and HuGE Navigator were searched up to May 1, 2014, using a combination of genetic and phenotype key words, including “nocturia,” “incontinence,” “overactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 68 publications
2
67
1
10
Order By: Relevance
“…It is possible that women with advanced POP experience more obstructive urinary symptoms, as reported by Rosenzweig et al [34] and Raz et al [35]. Family studies and twin studies have demonstrated that LUTS and POP are both heritable [33]. Our study, however, is crosssectional, and the risk factors we identified cannot be considered established causes of LUTS.…”
Section: 2contrasting
confidence: 54%
See 1 more Smart Citation
“…It is possible that women with advanced POP experience more obstructive urinary symptoms, as reported by Rosenzweig et al [34] and Raz et al [35]. Family studies and twin studies have demonstrated that LUTS and POP are both heritable [33]. Our study, however, is crosssectional, and the risk factors we identified cannot be considered established causes of LUTS.…”
Section: 2contrasting
confidence: 54%
“…The close relationship between LUTS and POP has rarely been explored. Having either incontinence or prolapse may be associated with an increased risk of developing the other condition [33]. It is possible that women with advanced POP experience more obstructive urinary symptoms, as reported by Rosenzweig et al [34] and Raz et al [35].…”
Section: 2mentioning
confidence: 89%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Women who develop symptoms may present with a single symptom such as feeling a vaginal bulge or pelvic pressure, or they may present with a combination of symptoms. 23 Loss of normal vaginal support occurs in most women with advancing age, particularly if they have had children.…”
Section: How Do Women With Pelvic Organ Prolapse Present?mentioning
confidence: 99%
“…Utiliza-se o termo Síndrome de hipermobilidade articular, quando há uma combinação de sinais e sintomas extraesqueléticos e musculoesqueléticos que incluem um número abrangente de disfunções, destacando entre elas a disfunção pélvica (2) . Disfunção do diafragma da pelve é uma condição que interfere diretamente na qualidade de vida e inclui a incontinência fecal, dor pélvica, disfunções sexuais, incontinência urinária (IU) e prolapso de órgãos pélvicos (POP), sendo os dois últimos considerados imensamente prevalentes (3) . Em meio a uma carência literária na genética molecular de IU e POP, despertou-se maior empenho sobre polimorfismos de outro tipo de colágeno I α1 (COL1A1) ou colágeno tipo III α1 (COL3A1).…”
Section: Introductionunclassified